Early development of the mesencephalic trigeminal nucleus. - Hunter, E; Begbie, J; Mason, I; Graham, A (2001)
The cells of the mesencephalic trigeminal nucleus (MTN) are the proprioceptive sensory neurons that innervate the jaw muscles. Interestingly, their evolution is generally thought to have been concomitant with that of the jaws. They are also the first born neurons of the mesencephalon, and their axons pioneer some of the major tracts within the brain. The cells of the MTN are also paradoxical in being the only group of intramedullary primary sensory neurons in amniotes. However, we know little about the early development of these important neurons, and we have analysed this here. To study the earliest stages of MTN development, we have used a battery of neural crest markers to try and pinpoint the progenitors of the MTN. We find that, contrary to current perceptions, the progenitors of the MTN are not highlighted by these markers, suggesting that they are not neural crest derived. However, the cells of the MTN are marked by means of their expression of Brn-3a. This gene labels cells that arise either side of the dorsal midline, extending rostrally from the isthmus across the roof of the mesencephalon. We have further demonstrated that the MTN develops under the influence of the Fgf-8 secreted by the isthmus. Ectopic Fgf-8 application promotes MTN development, whereas inhibiting Fgf-8 function in vivo drastically affects MTN development.